MAKNA KEBEBASAN DAN TANGGUNG JAWAB MAHASISWA DALAM PENGAMBILAN KEPUTUSAN: PENDEKATAN KONSELING EKSISTENSIAL - Silva Ramadhanti; Alifia Febrianti; Nor Fatmah (CV. ADIBA AISHA AMIRA, 2026)
This study aims to understand how students interpret freedom and responsibility in the decision-making process through the perspective of existential counseling. The study employs a descriptive qualitative approach, involving five currently enrolled students as participants who were purposively selected based on their experiences in facing important decisions. Data were collected through open-ended interviews and analyzed through data reduction, category coding, and thematic interpretation. The findings indicate that freedom is viewed as an opportunity to make independent choices without pressure from others. However, this freedom is often accompanied by doubt, anxiety, fear of making mistakes, and a tendency to postpone decision-making. Meanwhile, responsibility is understood as an individual’s awareness of the various long-term consequences that may arise from the choices made. The uniqueness of this study lies in the finding that freedom and responsibility are two interrelated and inseparable aspects in the decision-making process. From a practical perspective, the results of this study provide insights for counseling services in helping students better understand themselves, accept existing uncertainties, and make decisions in a more conscious and responsible manner.